2010
DOI: 10.4065/mcp.2009.0562
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Paradox and Cardiorespiratory Fitness in 12,417 Male Veterans Aged 40 to 70 Years

Abstract: Fitness altered the obesity paradox. Overweight and obese men had increased longevity only if they registered high fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
110
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(124 citation statements)
references
References 43 publications
10
110
2
2
Order By: Relevance
“…However, the level of fitness might modulate the mortality risk of obesity. In fact, among those within the same strata of low, moderate, or high cardiorespiratory fitness, overweight and obese men consistently had lower mortality than normal weight men, in groups of middle-aged and older male veterans (McAuley et al 2010(McAuley et al , 2009. This is consistent with our results which showed that beyond the age of 65, in a cohort of high functioning older men and women, obesity operated in a different Table 4 Hazard ratios of allcause mortality according to adiposity measurement quintiles in men, further adjusted for number of medications and self-rated socioeconomic status, in addition to age, physical activity, smoker status, history of cancer, diabetes, and heart disease *p<0.05 Numbers are expressed as mean (SD) a The fourth quintile of relative abdominal fat had the lowest all-cause mortality direction regarding longevity than in midlife.…”
Section: Discussionmentioning
confidence: 93%
“…However, the level of fitness might modulate the mortality risk of obesity. In fact, among those within the same strata of low, moderate, or high cardiorespiratory fitness, overweight and obese men consistently had lower mortality than normal weight men, in groups of middle-aged and older male veterans (McAuley et al 2010(McAuley et al , 2009. This is consistent with our results which showed that beyond the age of 65, in a cohort of high functioning older men and women, obesity operated in a different Table 4 Hazard ratios of allcause mortality according to adiposity measurement quintiles in men, further adjusted for number of medications and self-rated socioeconomic status, in addition to age, physical activity, smoker status, history of cancer, diabetes, and heart disease *p<0.05 Numbers are expressed as mean (SD) a The fourth quintile of relative abdominal fat had the lowest all-cause mortality direction regarding longevity than in midlife.…”
Section: Discussionmentioning
confidence: 93%
“…15 Investigators increasingly reference an obesity paradox among individuals with chronic diseases, whereby obese persons have higher survival rates compared to non-obese individuals. [16][17][18][19][20][21][22][23][24] Mechanisms for this obesity paradox are not fully understood, but proposed explanations include: 1) sick individuals lose weight and become frail as a result of underlying illnesses that cause wasting; 25 2) obese, sick individuals may have greater cardiorespiratory fitness (a proxy for physical wellness) than non-obese individuals who are also sick, but more likely to be frail and unfit, 26 which is supported by a "surplus calorie theory" hypothesizing that the obese have increased calorie reserves resulting in higher serum lipid levels, less protein/muscle breakdown and less uremia; 27 3) healthy individuals without major disease or injuries experience monotonically increasing mortality risk from excess adiposity, and individuals with major diseases or injuries experience monotonically decreasing mortality risk from excess adiposity; 28,29 4) older obese individuals receive more aggressive treatment that may lead to a potentially false appearance that obesity is protective; and 5) methodological concerns related to residual confounding, survivor bias, and lead-time bias. 25,[30][31][32] Regarding diabetes, it is widely acknowledged that body weight can be influenced by disease duration and weight loss (both intentional and unintentional) following diabetes development/diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has been made in healthy men and women, those with suspected or known CVD, and those with comorbid conditions, including obesity, T2DM, hypertension, and lipid abnormalities. [12][13][14][15][16][17][18][19][20][21][22][23] In a growing number of studies, CRF has been demonstrated to be a more powerful predictor of mortality risk than traditional risk factors such as hypertension, smoking, obesity, hyperlipidemia, and T2DM. In addition, CRF has been shown to be a more powerful predictor of risk than other exercise test variables, including ST-segment depression, symptoms, and hemodynamic responses.…”
Section: Overview Of Crf and Health Outcomesmentioning
confidence: 99%